Zoneamento sócio ambiental participativo do lugar denominado caça e pesca-Fortaleza/Ce, contribuição ao desenvolvimento sustentável da capital cearense - Silva, Marco Antonio Krichanã da (2004)
This research aimed the production of organized information, in an elementary level, concerning the Caça e Pesca neighbourhood — which comprehends ocean beaches, the estuary of a river crossing a considerably large area within the Metropolitan Area of the capital of the State of Ceará, in Northeast Brazil, and also a vast mangrove camp, dune fields and a stretch of transition forest —, located in the Eastern coast of the city of Fortaleza, due to the lack of organized relevant and updated data. Nonetheless, it constitutes a body of knowledge that can operate as a tool to promote initiatives destined to ensue a sustainable relationship between the local people, the environment and the urban development dynamics verified. The results shall provide the public administration with some essential data to subsidize environmental education actions and the adequate monitoring, desirably performed by the community itself, of the existing ecosystems, in relation to the urgent need of their preservation and, also imperative, the definition of sustainable tourism standards specially designed to fit the wholeness characterized by that area. The construction of a participative socioenvironmental diagnosis thus detaches the human occupation of that neighbourhood in space and time, complemented by a mapping approach of the geomorphological, hydrogeological and vegetal covering specificities of the region, in close relationship with the current socio-economic and socio-environmental aspects. A booklet following these results was published, in order to display basic data to the local community involved.